Ethical and legal issues in neurology - Beresford, H. Richard, 1930; Bernat, James L (Edinburgh : Elsevier, 2013)
"Advances in our understanding of the brain and rapid advances in the medical practice of neurology are creating questions and concerns from an ethical and legal perspective. Ethical and legal issues in neurology provides a detailed review of various general aspects of neuroethics, and contains chapters dealing with a vast array of specific issues such as the role of religion, the ethics of invasive neuroscience research, and the impact of potential misconduct in neurologic practice. The book focuses particular attention on problems related to palliative care, euthanasia, dementia, and neurogenetic disorders, and concludes with examinations of consciousness, personal identity, and the definition of death"-- Publisher's description
Research involving human subjects -- Clinical research in the developing world -- The ethics of invasive neuroscience research -- The ethics of neuro-enhancement -- Ethical issues in research neuroethics -- Legal issues in research neuroethics -- Social issues in neuroethics -- Neurophilosophy of consciousness -- Neurophilosophy of personal identity -- The definition of death
Includes bibliographical references and index
1 10
Keywords: Forensic neurology; Neurology -- Moral and ethical aspects; Neurologie -- Législation; Neurology -- ethics; Neurology -- legislation & jurisprudence; Neurologie -- éthique; Neurologie -- législation et jurisprudence